Pengembangan media jejak kaki hewan untuk pendidikan jasmani guna meningkatkan keterampilan keseimbangan pada anak berkebutuhan khusus - Hafidz Mukti Ramadhan; Mu’arifin Mu’arifin; Imam Hariadi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Children with autism often experience difficulties in motor coordination, attention, and responding to verbal instructions, which makes participation in physical education (PE) challenging. Studies show that their involvement in physical activities is significantly lower than that of typically developing children, limiting opportunities to improve balance and coordination—skills essential for independence and social participation. Moreover, most PJOK (Physical Education, Sports, and Health) learning media in special schools still rely on static visuals and verbal explanations, which fail to meet the sensory and attention needs of autistic students. Therefore, this study was conducted to address this gap by developing and validating animal footprint-based instructional media that provide adaptive, engaging, and movement-centred learning experiences. Fifty-five students from two special schools in Tapin Regency participated in this study through purposive sampling. Research instruments included expert validation sheets to assess content suitability, teacher questionnaires to evaluate practicality, and student performance checklists to measure the improvement in balance. Data were analyzed using descriptive statistics and a paired sample t-test. Results indicated that the media were highly valid (85.34%) and significantly improved motor balance (p = 0.002 < 0.05). The findings confirm that animal footprint-based media are valid, practical, and effective tools for improving motor balance in autistic learners.